1975
DOI: 10.1007/bf00421299
|View full text |Cite
|
Sign up to set email alerts
|

Dependence to morphine in differentially housed rats

Abstract: Although the effects of differential housing, particularly isolation, on the action of several classes of pharmacological agents have been studied, little attention has been given to this factor in regard to narcotics. The present study involves the effects of long-term social isolation on dependence to morphine produced by pellet implants in rats. When abstinence was precipitated with naloxone, isolated rats demonstrated less jumping and less diarrhea then grouped rats. No differences were found in other sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1977
1977
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Regarding the age, previous studies primarily focusing on morphine and heroin suggest that exposure to opioid during adolescent leads to decreased opioid withdrawal severity, which could be reversed by re-exposure during adulthood ( Windisch and Kreek, 2020 ). In contrast, the social influence on opioid withdrawal severity is more complex and may depend on behavioral procedure ( Adler et al, 1975 ; Coudereau et al, 1997 ; Broseta et al, 2005 ; Balter and Dykstra, 2012 ) or the drug history of the social peers ( Windisch and Kreek, 2020 ). Another question for future studies is that whether the effect observed in our study also generalize to female rats.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the age, previous studies primarily focusing on morphine and heroin suggest that exposure to opioid during adolescent leads to decreased opioid withdrawal severity, which could be reversed by re-exposure during adulthood ( Windisch and Kreek, 2020 ). In contrast, the social influence on opioid withdrawal severity is more complex and may depend on behavioral procedure ( Adler et al, 1975 ; Coudereau et al, 1997 ; Broseta et al, 2005 ; Balter and Dykstra, 2012 ) or the drug history of the social peers ( Windisch and Kreek, 2020 ). Another question for future studies is that whether the effect observed in our study also generalize to female rats.…”
Section: Discussionmentioning
confidence: 99%
“…In the present experiments, isolated animals exhibit a decrease in fighting after naloxone compared with baseline levels, similar to the decrease observed with group-housed animals. Although it is known that isolated animals exhibit altered responsivity to morphine (Adler et al, 1975;Kostowski et al, 1977), it remains to be demonstrated that isolation of the adult rat produces chronic changes in an endogenous opioid system.…”
Section: Discussionmentioning
confidence: 99%
“…1999) social behaviour in rats depending on the time of isolation and testing. Isolation early in life can alter the mature animal's response to the analgesic properties of opioids (Adler et al . 1975; Kostowski et al .…”
Section: Introductionmentioning
confidence: 99%